Safety net or helping hand? The effect of job search assistance and compensation on displaced workers - Daniel Fackler; Jens Stegmaier; Richard Upward (Halle Institute for Economic Research (IWH), 2023)
We provide the first systematic evidence on the effectiveness of a contested policy in Germany to help displaced workers. So-called 'transfer companies' (Transfergesellschaften) employ displaced workers for a fixed period, during which time workers are provided with job-search assistance and are paid a wage which is a substantial fraction of their pre-displacement wage. Using rich and accurate data on workers' employment patterns before and after displacement, we compare the earnings and employment outcomes of displaced workers who entered transfer companies with those that did not. Workers can choose whether or not to accept a position in a transfer company, and therefore we use the availability of a transfer company at the establishment level as an IV in a model of one-sided compliance. Using an event study, we find that workers who enter a transfer company have significantly worse post-displacement outcomes, but we show that this is likely to be the result of negative selection: workers who lack good outside opportunities are more likely to choose to enter the transfer company. In contrast, ITT and IV estimates indicate that the use of a transfer company has a positive and significant effect on employment rates five years after job loss, but no significant effect on earnings. In addition, the transfer company provides significant additional compensation to displaced workers in the first 12 months after job loss.
urn:nbn:de:gbv:3:2-988488
Keywords: J63; J65; J68; 330; earnings; employment; job loss; transfer companies